Regulador vegetal influencia o potencial fitorremediador de metal pesado em plântulas? - Carvalho, Rafael Miranda de Lima (Universidade Federal de São Carlos, 2023)
Cadmium (Cd) is a mineral considered a non-essential heavy metal (HM) and is widespread in the 6 environment due to a range of inadequate anthropogenic activities such as industrialization, 7 urbanization, and unplanned agriculture. In plants, exposure to Cd is associated with a range of 8 morpho-physiological disorders including necrosis in roots, stems, leaves, as well as impairment of 9 respiratory, photosynthetic, enzymatic processes, and increased production of reactive oxygen 10 species (ROS). Phytoremediation is an ecological strategy that uses plants accumulator to stabilize, 11 transfer, or degrade environmental pollutants. Despite the relevance and importance of 12 phytoremediation on a global scale, the literature reports conflicting results on the interaction 13 between botanical genus Solanum species and compounds that stimulate phytoremediation, such as 14 plant growth regulators (PGR). Therefore, we decided to address this research in a previous 15 Scientific and Technological Initiation (STI) experiment, which resulted in preliminary 16 experimental data used for the present monograph written in the scientific format 'short 17 communication'. The null hypothesis (H0) consisted on the use of PGR not reducing the 18 phytoremediation potential of seedlings cultivated with heavy metal presence. On the other hand, 19 the alternative hypothesis (H1) consisted on the use of PGR reducing the phytoremediation potential 20 of seedlings cultivated with heavy metal presence. The data from this manuscript elucidated the 21 ability of the PGR to promote the plant defense against abiotic stresses with antioxidant responses, 22 but do not support the hypothesis of the ability to interfere positively or negatively with the 23 phytoremediation potential.
Do plant growth regulator improved the heavy metals phytoaccumulation potential of accumulating seedlings?
Keywords: EROs; Fisiologia Vegetal; Fitorremediação; Iniciação científica e tecnológica; Metal pesado; Heavy metal; Plytoremediation; Plant physiology; ROS; Scientific and tecnologigal; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL